2017
DOI: 10.1016/j.msec.2016.11.107
|View full text |Cite
|
Sign up to set email alerts
|

Novel ultrasound-responsive chitosan/perfluorohexane nanodroplets for image-guided smart delivery of an anticancer agent: Curcumin

Abstract: Ultrasound-responsive nanodroplets are a class of new emerging smart drug delivery systems which provide image-guided nano-therapy of various diseases, especially cancers. Here, we developed multifunctional smart curcumin-loaded chitosan/perfluorohexane nanodroplets for contrast-ultrasound imaging and on-demand drug delivery. The nanodroplets were synthesized via nanoemulsion process. The optimal formulation with the size of 101.2nm and 77.8% curcumin entrapment was chosen for release study and cytotoxicity ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…As an example, perfluorohexane nanodroplets with the shell of chitosan were synthesized through emulsion chemistry, and were subsequently loaded with curcumin [101]. The loaded nanodroplets were successfully able to have on-demand release the drug in response to external ultrasound stimuli.…”
Section: Ultrasound-responsive Drug Releasementioning
confidence: 99%
“…As an example, perfluorohexane nanodroplets with the shell of chitosan were synthesized through emulsion chemistry, and were subsequently loaded with curcumin [101]. The loaded nanodroplets were successfully able to have on-demand release the drug in response to external ultrasound stimuli.…”
Section: Ultrasound-responsive Drug Releasementioning
confidence: 99%
“…The in vitro release studies showed that 63.5% of the incorporated curcumin was released over 4 min by sonication at a frequency of 1 MHz. Cytotoxicity studies showed that Cur/chitosan/PFH nanodroplets in the presence of ultrasound induce toxic effects in 4T1 cancer cells (Baghbani et al, 2017). which is beneficial for biomedical applications.…”
Section: Chitosan-based Stimuli-sensitive Formulationsmentioning
confidence: 99%
“…Baghbani et al [ 93 ] developed smart curcumin-loaded chitosan/perfluorohexane nanodroplets capable of several functions. These nanodroplets were developed for contrast-ultrasound imaging and evaluated its cytotoxicity in vitro on 4T1 human breast cancer cells.…”
Section: Ultrasonography Imagingmentioning
confidence: 99%